The Effect of Integrity and Work Discipline on Employee Engagement: Motivation as an Intervening Variable - Djoko Soelistya; Ade Septiarisna Warindra; Muhammad Rosyihudin; Moch Indah Hastomo Nugroho (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The development of the business world in the era of globalization has made the business competition map more competitive. The company generally aims to earn operating profit and seeks to maintain and develop the viability of the business itself and find solutions because the Plastic Woven Packaging Manufacturing Company in Gresik, has problems with a decrease in employee performance, This study aims to analyze the effect of employee integrity and discipline in improving their performance through their work motivation. And the following research applies quantitative methods using a population of employees of the Plastic Woven Packaging Manufacturing Company in Gresik which uses a sample of 100 employees from the production department. The results of the following study provide evidence that the effect of (1) work integrity has a significant direct effect on performance (2) work discipline also has a significant direct influence on performance (3) work integrity has a significant direct effect on work motivation and (4) work discipline also affects significantly directly on work motivation while (5) work motivation has a significant direct effect on performance,and for the results of the indirect effect through the mediating variable of work motivation that (6) Integrity has a significant direct effect and can improve employee performance although not through work motivation as a mediating variable while (7) Work discipline has no significant effect and can improve employee performance directly even though not through work motivation as a mediating variable.